The Role of Innovation Management in the Modern World Economy (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Innovation is one of the important forms of expanding the capabilities of the economic system in the modern world. On the basis of innovation, science, production and the market are being united. In recent years, innovation has transformed from an element of economic development into a general social factor in the development of regions. Innovation management can be recognized as a multifunctional activity. The object of this activity is a number of factors, including the economic, organizational, managerial, legal and psychological impact on the processes of innovation, and ways to most effectively organize the implementation of innovations and innovative developments. This article presents the essence of innovation management, its significance and role in the modern world economy.